Perspective on COVID-19 vaccination in patients with immune-mediated kidney diseases: consensus statements from the ERA-IWG and EUVAS. Issue 8 (4th March 2022) - Stevens, Kate I; Frangou, Eleni; Shin, Jae I l; Anders, Hans-Joachim; Bruchfeld, Annette; Schönermarck, Ulf; Hauser, Thomas; Westman, Kerstin; Fernandez-Juarez, Gema M; Floege, Jürgen; Goumenos, Dimitrios; Turkmen, Kultigin; et al.
ABSTRACT: Patients with immune-mediated kidney diseases are at increased risk of severe coronavirus disease 2019 (COVID-19). The international rollout of COVID-19 vaccines has provided varying degrees of protection and enabled the understanding of vaccine efficacy and safety. The immune response to COVID-19 vaccines is lower in most patients with immune-mediated kidney diseases; either related to immunosuppression or comorbidities and complications caused by the underlying disease. Humoral vaccine response, measured by the presence of antibodies, is impaired or absent in patients receiving rituximab, mycophenolate mofetil (MMF), higher doses of glucocorticoids and likely other immunosuppressants, such as cyclophosphamide. The timing between the use of these agents and administration of vaccines is associated with the level of immune response: with rituximab, vaccine response can only be expected once B cells start to recover and patients with transient discontinuation of MMF mount a humoral response more frequently. The emergence of new COVID-19 variants and waning of vaccine-induced immunity highlight the value of a booster dose and the need to develop mutant-proof vaccines. COVID-19 vaccines are safe, exhibiting a very low risk of de novo or relapsing immune-mediated kidney disease. Population-based studies will determine whether this is causal or coincidental. Such cases respond to standard management, including the use of immunosuppression. The Immunonephrology Working Group and European Vasculitis Society recommend that patients with immune-mediated kidney diseases follow national guidance on vaccination. Booster doses based on antibody measurements could be considered.